The Responses of Mathematics Pre-Service Teachers Toward Online Lectures in the Covid-19 Era - Imaludin Agus; Amanda La Hadi (Edumatika : Jurnal Riset Pendidikan Matematika, 2020)
Abstract. Covid-19 pandemic had affected in paradigm changing of learning from face-to-face to online learning. It was not easily adapted by educators or students. This study aims to assessed responses from mathematics pre-service teachers about online lectures during the covid 19 outbreak. The research was a descriptive survey design that was conducted on 75 selected semester II-VI of math students in IAIN Kendari. Responses were obtained by questionnaires and interviews that further were collected, sorted, and categorized base on an online lecture platform. Our finding reveals that WhatsApp becomes the most entry and frequently platform that used in lectures (65.3%), followed by Google Classroom (18.7%), YouTube (2.7%), e-mail (2.7%), Facebook (1.3%), and a combination of several media (9.3%), while Zoom in the least preferred. The obstacles faced by students during online learning were poor internet connection, internet quota requirements, and limited online lecturing equipment. However, the possibility to study anywhere (home, garden, beach, etc.) and flexible learning time is the ease gained by the students in these methods. Meanwhile, in terms of effectiveness, we found some different responses including very effective (1.3%), effective (12%), less effective (78.7%), ineffective (2.7%), and very ineffective (5.3%). Generally, most mathematics students (60%) responded they want to meet face to face, and only 2.7% of them want online learning, and (37.3%) want blended learning. Based on these results, blended learning could be a choice in the lecture by more attractive online media. Abstrak. Pandemi covid-19 berdampak pada perubahan paradigma belajar dari tatap muka menjadi pembelajaran online. Hal ini tidak mudah diadaptasi oleh pendidik maupun peserta didik. Oleh karena itu, penelitian ini bertujuan untuk memperoleh tanggapan calon guru matematika tentang perkuliahan online di era pandemi covid-19. Penelitian ini merupakan penelitian survey deskriptif dengan sampel dipilih secara purposive sebanyak 75 mahasiswa tadris matematika IAIN Kendari semester II-VI. Data diperoleh dengan menggunakan angket dan wawancara. Analisis data dilakukan dengan cara mengumpulkan, mengurutkan, dan mengkategorisasi. Berdasarkan data tersebut diperoleh bahwa platform online yang sering digunakan dalam perkuliahan diera covid-19 adalah WhatsApp (65,3%), google clasroom (18,7%), YouTube (2,7%), e-mail (2,7%), facebook (1,3%), dan kombinasi beberapa media (9,3%), dengan WhatsApp sebagai media online yang paling disukai dan Zoom yang tidak disukai. Hambatan yang dihadapi mahasiswa selama pembelajaran online yaitu jaringan internet yang terbatas, membutuhkan quota internet yang banyak, dan perangkat perkuliahan online yang minim, sedangkan kemudahan yang diperoleh yaitu dapat belajar dimana saja (rumah, kebun, pantai, dll) serta waktu belajar yang tidak terbatas. Keefektifan perkuliahan online yaitu sangat efektif (1,3%), efektif (12%), kurang efektif (78,7%), tidak efektif (2,7%) dan sangat tidak efektif (5,3%). Secara umum, mahasiswa tadris matematika memberikan tanggapan bahwa ketika pandemi covid-19 berakhir (60%) mahasiswa menginginkan tatap muka, (2,7 %) menginginkan online, dan (37,3%) mengingikan blended learning. Berdasarkan hasil tersebut maka blended learning bisa menjadi alternatif pilihan dalam proses perkuliahan dengan mempergunakan media online yang lebih menarik.